The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fpls.2022.932793
|View full text |Cite
|
Sign up to set email alerts
|

Highly Overexpressed AtC3H18 Impairs Microgametogenesis via Promoting the Continuous Assembly of mRNP Granules

Abstract: Plant CCCH zinc-finger proteins form a large family of regulatory proteins function in many aspects of plant growth, development and environmental responses. Despite increasing reports indicate that many CCCH zinc-finger proteins exhibit similar subcellular localization of being localized in cytoplasmic foci, the underlying molecular mechanism and the connection between this specific localization pattern and protein functions remain largely elusive. Here, we identified another cytoplasmic foci-localized CCCH z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 53 publications
(61 reference statements)
1
9
0
Order By: Relevance
“…After HS, excitingly, it was observed high temperature changed GFP-LlC3H18 from being mainly dispersed in the cytoplasm to being aggregated into cytoplasmic foci, which was consistent with the distribution of the mCherry fluorescence of the PB marker mCherry-DCP2 and the SG maker mCherry-PABP8 (Fig. 2 A) (Decker and Parker 2012 ; Xu et al 2022 ). Due to both PB and SG are the mRNP granules, so these results indicated that LlC3H18 exhibited variable subcellular localization characteristics and may play roles in mRNA regulation with RNA-binding ability.…”
Section: Resultssupporting
confidence: 77%
See 3 more Smart Citations
“…After HS, excitingly, it was observed high temperature changed GFP-LlC3H18 from being mainly dispersed in the cytoplasm to being aggregated into cytoplasmic foci, which was consistent with the distribution of the mCherry fluorescence of the PB marker mCherry-DCP2 and the SG maker mCherry-PABP8 (Fig. 2 A) (Decker and Parker 2012 ; Xu et al 2022 ). Due to both PB and SG are the mRNP granules, so these results indicated that LlC3H18 exhibited variable subcellular localization characteristics and may play roles in mRNA regulation with RNA-binding ability.…”
Section: Resultssupporting
confidence: 77%
“…Similar to the protein structure of Arabidopsis AtC3H18 (Xu et al 2022 ), LlC3H18 has a CCCH domain and two potential RBDs (Fig. S 3 ).…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Another Arabidopsis CCCH ZFP gene, AtC3H18 , is predominantly expressed in the developing microspores, and its gain-of-function mutant exhibited a male sterility phenotype. Further investigation suggested that AtC3H18 may modulate pollen mRNA by regulating the assembly/disassembly of messenger ribonucleoprotein (mRNP) granules, thereby affecting pollen development [ 146 ]. CCCH ZFP genes BcMF30a and BcMF30c are substantially expressed during microgametogenesis and pollen germination in B. campestris .…”
Section: Roles Of Tfs In Male Gametophyte Developmentmentioning
confidence: 99%